Dinamika Politik Islam di Era Globalisasi: Tantangan Masa Depan: Future Challenges - Fitri Mawardah, Ni Nyoman; Gustiana, Amanda Laila; Maharani, Diva; Julia, Navysha Putri; Irawan, Raissa Auliya Sharfina; Hidayat, Arif (Universitas Muhammadiyah Surabaya, 2025)
The dynamics of Islamic politics in the era of globalization have become an increasingly relevant topic in light of worldwide social, economic, and technological changes. Globalization, with all its impacts, has influenced how Muslims perceive and practice politics, both at the local and international levels. This article aims to analyze how globalization affects the development of Islamic politics, including the challenges and opportunities that arise. The research method used is a literature study with a qualitative approach, gathering data from various sources such as journals, books, and related reports. The findings indicate that globalization has accelerated the exchange of ideas and values between the Islamic world and the West, creating polarization between modernization and conservatism in Islamic politics. On one hand, globalization promotes integration and intercultural dialogue, while on the other, it triggers resistance and efforts to preserve Islamic identity. This article also discusses how Islamic political actors, such as political parties and social movements, respond to the challenges of globalization with various strategies, ranging from adaptation to outright rejection. In conclusion, the dynamics of Islamic politics in the era of globalization reflect a complex interaction between tradition and modernity, requiring a deep understanding of both local and global contexts to formulate effective and inclusive policies.